Colistin residue in broiler: detection in different growth stages - Bristy, Naima Islam; Das, Sajal; Noman, Zakaria al; Ferdous, Jannatul; Sachi, Sabbya; Kabir, S M Lutful; Sikder, Mahmudul Hasan (Asian-Australasian Journal of Food Safety and Security, 2019)
Indiscriminate use of antibiotics in broiler could lead to residue accumulation in food chain. We conducted a study to detect colistin residues in broiler meat in different growth stages, collected from different upazilas of Mymensingh division. A total of 108 samples, were collected from Fulbaria, Mymensingh Sadar, and Trishal Upazila of Mymensingh district and Nakla Upazila of Sherpur district. From each farm, nine samples were collected at the three different growth stages: 14-20 days (Early:E), 21-27 (Middle:M) days and 28-35 (Late:L) days, respectively. Thin layer chromatography (TLC) was used for the qualitative detection colistin residues in broiler meat. A questionnaire survey was carried out with the farmers from whom the samples were collected. Most of the farmers’ had varying degree of knowledge about biosecurity, withdrawal period and residue of antibiotic, and academic qualification varies from primary to graduate level. Out of 108 samples, 50% (18 out of 36) samples were positive for TLC in early samples, whereas 66.67% (24 out of 36) samples for middle and 50% (18 out of 36) for late collected samples. Upazila-wise, the highest concentration was detected in Mymensingh sadar and Nakla (66.67%) and lowest in Fulbaria (33.33%). These result indicates that colistin are being misused in poultry industry especially in middle days of broiler life and withdrawal periods are not maintained when broiler are marketed. Being a Reserve group antibiotics, measures are needed to ensure human safety regarding colistin residue in poultry industry. Asian Australas. J. Food Saf. Secur. 2019, 3(1), 43-47